2023
DOI: 10.3390/agriculture13091717
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the Dietary Replacement of Soybean Oil with Rubber Seed Oil on the Growth Performance, Carcass Trait, and Status of Lipid Metabolism in Pekin Ducks

Zitao Zhao,
Yanhong Guo,
Lei Zhuang
et al.

Abstract: The objective of this study is to determine the effects of the dietary replacement of soybean oil (SO) with rubber seed oil (RSO) on the growth performance, carcass trait, and lipid metabolism in Pekin ducks. A total of 160 1-day-old Pekin ducks were randomly allocated to four experimental treatments and fed diets with different ratios of SO to RSO as follows: 3:0 (control), 2:1, 1:2, and 0:3. Dietary RSO supplementation had no effect on their growth performance; however, it significantly decreased the yield o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…26% of total fat), which gives them the opportunity to be used in animal feed not only as a concentrated source of energy but also as a potential resource to obtain food products of animal origin enriched in n-3 PUFA (functional foods). Zhao et al [18] demonstrated that replacing soybean oil with rubber seed oil reduced abdominal fat deposition and increased n-3 PUFA levels in meat without affecting the growth performance of Pekin ducks. In addition to nutritional factors, the housing system can influence productive performance, carcass traits, and bone composition in ducks.…”
mentioning
confidence: 99%
“…26% of total fat), which gives them the opportunity to be used in animal feed not only as a concentrated source of energy but also as a potential resource to obtain food products of animal origin enriched in n-3 PUFA (functional foods). Zhao et al [18] demonstrated that replacing soybean oil with rubber seed oil reduced abdominal fat deposition and increased n-3 PUFA levels in meat without affecting the growth performance of Pekin ducks. In addition to nutritional factors, the housing system can influence productive performance, carcass traits, and bone composition in ducks.…”
mentioning
confidence: 99%